Conducting Job Analysis And Performance Appraisal System In Rumah Makan Jodoh - Delicia Olivian; Agustinus Setyawan (Universitas Internasional Batam, 2023)
Human resources are one of the most important assets owned by a business. In running a business, business owners have an obligation to ensure that human resources are able to carry out their job and responsibility precisely as well as efficiently. This can be done with job analysis, by analysing the work of each position the owner can obtain job description along with job description. Job analysis can make it easier for owners to choose the suitable human resources that are suited in one work position. As the business goes on, there is time to measure employee performance. Hence, there is a need to conduct a system that can make it easier for the owner to make an assessment by implementing performance appraisal system. Assessment indicators can be obtained from job descriptions that is obtained when carrying out job analysis. By carrying out job analysis and implementing the system, businesses can improve the overall employee work efficiency. On this research, job analysis and performance appraisal system were carried out at Rumah Makan Jodoh which is a micro business that sells various of Chinese and Indonesians cuisine. Rumah Makan Jodoh had been established since 2004. The method used in this research was observation and interviews with business owner. From the process of interviewing with owner it became aware that there is no precise responsibility of each position of the workers, therefore in this research will be conducting job analysis and implementing performance appraisal system to increase the overall work efficiency. This implementation lasted for three months. The results of this implementation were declared successful and the initial goal was achieved, which is placing the right employees in the right positions. The business owner also stated that this implementation had increased the overall work efficiency of employees.